'It feels it's wasting whatever time I've got left': A qualitative study of living with treatable but not curable cancer during the COVID-19 pandemic. (January 2022) - Radcliffe, Eloise; Khan, Aysha; Wright, David; Berman, Richard; Demain, Sara; Foster, Claire; Restorick-Banks, Susan; Richardson, Alison; Wagland, Richard; Calman, Lynn
Background: People living with cancer that is treatable but not curable have complex needs, often managing health at home, supported by those close to them. Challenges are likely to be exacerbated during the COVID-19 pandemic and the risk-reducing measures introduced in response. The impact of COVID-19 on those living with incurable, life-threatening conditions is little understood. Aim: To investigate the experiences and identify the impact of the COVID-19 pandemic for people living with treatable not curable cancer and their informal carers. Design: Qualitative semi-structured phone interviews were conducted with 21 patients living with cancer that is treatable but not curable and 14 carers. Setting/ participants: Participants were part of a larger longitudinal qualitative study (ENABLE) on supported self-management for people living with cancer that is treatable but not curable. Results: The COVID-19 pandemic magnified uncertainty and anxiety and led to loss of opportunities to do things important to patients in the limited time they have left to live. Lack of face-to-face contact with loved ones had a significant impact on patients' and carers' emotional wellbeing. Carers experienced increased responsibilities but less access to formal and informal support and respite. While changes to treatment led to some concern about longer-term impact on health, most patients felt well-supported by healthcare teams. Conclusion: The study provides rich insights into the nature of challenges, uncertainty and lost opportunities resulting from the COVID-19 pandemic for patients and carers living with cancer that is treatable but not curable, which has wider resonance for people living with other life-limiting conditions.